Exploration of fishing gears and temporal distribution of fish species at Shibsa River, Paikgachha, Bangladesh (Journal of the Bangladesh Agricultural University, 2020)
The present study was undertaken to ascertain fishing gear and craft uses, fish catch composition of the particular gear along with the identification of available fish species of Shibsa River, South-Western Bangladesh for a period of 12 months from January to December, 2018. From the present study, 15 distinct fishing gears under 8 major groups including berj al, chandi jal and current jal were dominantly encountered. Precisely 60 fish species (55 finfish and 5 shellfish) were listed covering 28 families of which Cyprinidae was found as most dominant having 13 species followed by Bagridae, Channidae, Clupeidae, Siluridae, Gobiidae, Palaemonidae, Ambassidae, Cichlidae and the rest of the families having only one single species under a single genera for each. This study also depicted 8 endangered (14%), 5 vulnerable (8%), 33 least concern (55%), 8 near threatened (13%) and 6 not evaluated (10%) species out of 55 finfish and 5 shellfish species. Due to incognizance and over exploitation on fish with small mesh size net, species diversity of this river is under threat. So, public awareness and compatible knowledge on use of suitable fishing gears with suitable mesh size could contribute to sustainable fisheries in this river and betterment in livelihood of the fishermen in the surrounding area.J Bangladesh Agril Univ 18(1): 157–164, 2020https://doi.org/10.5455/JBAU.94755